Шляхи підвищення ефективності компенсації реактивної потужності в системах електропостачання промислових підприємств - Коваленко, Олександр Іванович; Kovalenko, Oleksandr; Коваленко, Любов Рафаїлівна; Kovalenko, Lyubov (Запоріжжя: ТДАТУ, 2025)
UA: Значна кількість електроенергії витрачається під час її транспортування. Основними спожи-вачами електроенергії є промислові підприємства. Компенсація реактивної потужності (далі – РП) в систе-мі електропостачання дає змогу забезпечити баланс активної та реактивної потужності, знизити втрати та поліпшити показники якості електричної енергії. Під час компенсації РП необхідно передбачати регульовані джерела РП. Проаналізовано схеми компенсації РП із використанням конденсаторних батарей та статичних тиристорних компенсаторів. Відзначено переваги та недоліки схем. Розроблено комбіновану схему регульо-ваного джерела РП. Схема забезпечує високу швидкість та ефективність регулювання потужності, низький уміст вищих гармонік струму. /// EN: This article presents the volumes of generation and consumption of electrical energy in Ukraine. Up to 19% of electrical energy is expended during its transmission. The principal consumers of electrical energy are industrial enterprises. For them, increasing energy efficiency and reducing losses of electrical energy in power supply networks are pressing tasks. Compensation of reactive power in the power supply system makes it possible to: ensure the balance of active and reactive power; reduce losses of electrical power; improve power quality indices. Methods of voltage regulation by altering reactive power flows are associated with ensuring its balance within the network. Voltage regulation at the nodes of an enterprise’s distribution network and directly at the terminals of electrical loads is performed by changing the voltage drops in the elements of the electrical network by regulating the flows of reactive power. It is noted that, when compensating reactive power, it is necessary to provide controllable sources of reactive power to adjust the characteristic Q = f(U). At the system nodes, specified ratios between active and reactive power must be maintained. Schemes of reactive power compensation are analysed: capacitor banks without power regulation; capacitor banks with stepwise power regulation; capacitor banks regulated by a thyristor-reactor group – static VAR compensators; static VAR compensators with stepwise controllable capacitance. The advantages and disadvantages of the schemes are noted. A combined scheme of a controllable source of reactive power has been developed. The scheme provides high speed and efficiency of power regulation, and a low content of higher current harmonics. Smooth regulation is achieved by regulating the inductive and capacitive components of reactive power. The main function of the source of reactive power is to regulate voltage in the enterprise’s electrical network, wherein the source generates or consumes reactive power. This makes it possible to obtain standardised power quality indices in the enterprise’s network, to relieve it of the transfer of reactive power, and to reduce active power losses.
Ways to increase the efficiency of reactive power compensation in the power supply systems of industrial enterprise
Keywords: утрати активної потужності; компенсація реактивної потужності; схеми компенсації; регу-льоване джерело реактивної потужності; ctive power losses; reactive power compensation; compensation schemes; controllable source of reactive power